2016
DOI: 10.1016/j.ijsu.2016.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Adverse impact of low skeletal muscle index on the prognosis of hepatocellular carcinoma after hepatic resection

Abstract: Low-SMI was an independent adverse prognostic factor for CRR in patients with BMI ≥22. Therefore, preventing muscle wasting may improve the CRR of patients with HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
68
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 38 publications
7
68
2
Order By: Relevance
“…We enrolled 209 consecutive HCC patients with CLD from February 2013 to November 2016. Hospitalized HCC patients with CLD who met the following criteria were included: those 20 years of age or older, those with a performance status of grade 0 to 2, as defined by the Eastern Cooperative Oncology Group, and those treated with TACE . Patients were excluded if there was a risk of HCC rupture, they had hepatic encephalopathy grade 2–4 according to the West Haven Criteria, , there was a risk of esophageal varices rupture, they had heart failure, or they had respiratory failure …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We enrolled 209 consecutive HCC patients with CLD from February 2013 to November 2016. Hospitalized HCC patients with CLD who met the following criteria were included: those 20 years of age or older, those with a performance status of grade 0 to 2, as defined by the Eastern Cooperative Oncology Group, and those treated with TACE . Patients were excluded if there was a risk of HCC rupture, they had hepatic encephalopathy grade 2–4 according to the West Haven Criteria, , there was a risk of esophageal varices rupture, they had heart failure, or they had respiratory failure …”
Section: Methodsmentioning
confidence: 99%
“…Sarcopenia is defined as the generalized loss of muscle mass and muscle strength . Sarcopenia is frequently seen in patients with chronic liver disease (CLD), and it has an adverse impact on clinical outcomes, including poor quality of life, development of hepatocellular carcinoma (HCC), and poor survival rates …”
Section: Introductionmentioning
confidence: 99%
“…In terms of patient demographic characteristics, female patients accounted for 28.4% of the investigated population and the mean (or median) age of the enrolled patients in each study (or its subgroup) ranged between 57 and 73.9 years. Regarding the pattern of underlying malignancy, 7 studies included patients with resectable HCC [21][22][23][24][25][26][27], 3 included patients with any clinical stage of HCC [20,28,29], 1 included patients with primary liver tumors (69.8% had HCC) [30], 1 included patients with hepatic cancers (50.5% had HCC) undergoing intraarterial therapy [31], and 1 included patients with HCC following sorafenib treatment [32]. The muscle volume was estimated on the transverse CT image at the third lumbar vertebra level in all the selected studies, although the intensity window -(shown by using the Hounsfield scale) for recognizing skeletal muscles and cut-off points for sarcopenia -varied across trials ( Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The crude pooled HR of skeletal muscle mass loss for recurrence-free survival from 6 studies was calculated to be 1.85 (95% CI: 1.44-2.37) [21,22,24,[26][27][28], while the adjusted summary HR from 4 selected trials was 1.76 (95% CI: 1.27-2.45) (Fig. 5) [22,23,26,27]. The test for heterogeneity was not significant for both pooled values (I 2 < 0.001 and p value = 0.577 for the crude HRs; I 2 = 43.85 and p value = 0.148 for the adjusted HRs).…”
Section: Recurrence-free Survivalmentioning
confidence: 99%
“…Predefined cutoffs were adopted in 8 studies [11,20,[24][25][26][27][28]39], and optimum stratification, receiver operator characteristic curve and study-specific percentiles were used in the other studies [12-14, 21-23, 29-38, 40-42]. Sex-specific cutoffs were employed in almost all of the included studies, and on comparison with males, females showed a relatively lower muscle mass and MA (Table 3).…”
Section: Cutoff For the Sarcopenia Indexmentioning
confidence: 99%